(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides a comparative analysis of the use of measure words in phraseological units of the Uzbek and English languages using examples. In the process of studying phraseological units using examples, it turns out that arithmetic words are widely used in both languages and that they have their own meaning in different languages and play an important role in linguistics.